Association of dietary intake and lifestyle with body mass index and body fat percentage among University Tunku Abdul Rahman (UTAR), Kampar student - Teo, Lim Ang (2023)
Globalization and modernization have unfortunately resulted in unhealthy dietary patterns and a unhealthy lifestyle among Malaysians, leading to high levels of obesity and body fat. Thus, this research aimed to investigate the association between lifestyle, dietary intake with body mass index and body fat percentage among students in the Kampar campus of Universiti Tunku Abdul Rahman (UTAR). A convenience sampling method was employed to select the participants for a cross-sectional study that was conducted among 165 UTAR students. The study involved a guided self-administered online questionnaire and physical measurements. SPSS software was utilized to analyze the data. Pearson's Chi-Square test was employed to examine the association between dietary intake, lifestyle, body mass index, and body fat percentage of the respondents. It also used to identify the association between body mass index and body fat percentage. The present study found that there was a significant association between body mass index and body fat percentage (p<0.001). Regarding lifestyle, there was significant association between lifestyle with iii body mass index (p=0.002) and body fat percentage (p <0.001), For dietary intake with BMI, a significant association of BMI with vegetable (p<0.001), fruits (p<0.011), nuts (p<0.001) , red meat (p<0.001), processed food consumption (p<0.011), breakfast consumption (p=0.008), type of bread consumed (p<0.001) and frequency (p=0.042), type of milk consumption (p=0.004) was found. In terms of dietary intake with body fat percentage, there was a significant association between body fat percentage with vegetable (p <0.001), fruits consumption (p<0.001), red meat consumption (p<0.001), processed food consumption (p<0.001), type of bread consumed (p=0.008), type of milk consumption (p=0.004) and type of spread used in sandwich (p<0.001). Overall, the findings indicated that a healthy lifestyle and good dietary intake may produce a good BMI and body fat outcome.